Towards a More Holistic Comparative Assessment of Plant-Based Alternative Beverages and Dairy Milk: A True Cost Accounting Approach - Mauricio R. Bellon; Nicholas Benard; Jane E. Coghlan; Kathleen Merrigan (Foods)
There is a growing market for plant-based alternative beverages (PBAs) promoted as alternatives to dairy milk. Part of their popularity is that consumers consider them better for both the environment and human health. These perceptions, however, may not be entirely supported by scientific evidence. A holistic comparison of dairy milk and PBAs is difficult because their prices typically do not reflect their environmental and nutritional health impacts, although PBAs tend to be significantly more expensive than dairy milk. Here, we integrate key results from the scientific literature using a True Cost Accounting (TCA) approach to compare dairy milk and five PBAs based on their market retail price and a quantification—and when possible, monetization—of key environmental, nutritional, and social impacts: Global Warming Potential (GWP), dietary risks, and forced labor, respectively. We compare whole dairy milk with five PBAs: soy, almond, oat, coconut, and pea, which account for 97% of retail market sales in the USA. The results show that while environmental, nutritional, and social benefits attributed to PBAs compared to dairy milk exist and can be significant, they are heterogenous, and for some PBAs, they may not be as significant as commonly perceived, particularly when the price premium they command are considered.